Selecting mesophilic biodesulphurising microorganisms - MOGOLLÓN G., L. I.; MADERO G, A.; MORA. M, A. L.; OSORIO C., L. F. (CT&F - Ciencia, Tecnología y Futuro, 1998)
The development of biodesulfurization ( BDS) processes for hydrocarbons requires fast and reliable methods for the screening of microorganisms. This work shows the results of the screening process for indigenous Colombian strains with a BDS potential capacity. The main criteria for the screening was the qualitative and quantitative determination of 2-hydroxybiphenyl (2-HBP) as the typical metabolite of the 4S specific pathway. Microorganisms were cultured by two methodologies, A and B, using DBT as the model compound. The quantitative determination of metabolites was made by HPLC. Thirteen strains were evaluated, including the strain Rhodococcus rhodocrous IGTS8, by methods A and B. In method A, the inoculum was exposed to DBT since the beginning of the culture. Method B, employed two stages: (i) Growth period under limiting sulfur conditions, (ii) Transforming period, in which the pre-grown inoculum was exposed to the organic sulfur substrate. The culture of mesophilic microorganisms isolated by method B, served to find a mechanism for the organic sulfur metabolism, and the evaluation of the sulfur removal capability of five indigenous strains. In the cultures of these strains, 2- hydroxybiphenyl (2-HBP) was detected as a byproduct of DBT metabolism, both qualitatively and quantitatively.